Exploring the Plasmodium falciparum cyclic-adenosine monophosphate (cAMP)-dependent protein kinase (PfPKA) as a therapeutic target - Haste, Nina M. (2012)
One of the prototype mammalian kinases is PKA and various roles have been defined for PKA in malaria pathogenesis. The recently described phospho-proteomes of Plasmodium falciparum introduced a great volume of phospho-peptide data for both basic research and identification of new anti-malaria therapeutic targets. We discuss the importance of phosphorylations detected in vivo at different sites in the parasite R and C subunits of PKA and highlight the inhibitor sites in the parasite R subunit. The N-terminus of the parasite R subunit is predicted to be very flexible and we propose that phosphorylation at multiple sites in this region likely represent docking sites for interactions with other proteins, such as 14-3-3. The most significant observation when the P. falciparum C subunit is compared to mammalian C isoforms is lack of phosphorylation at a key site tail implying that parasite kinase activity is not regulated so tightly as mammalian PKA. Phosphorylation at sites in the activation loop could be mediating a number of processes from regulating parasite kinase activity, to mediating docking of other proteins. The important differences between Plasmodium and mammalian PKA isoforms that indicate the parasite kinase is a valid anti-malaria therapeutic target.